1991
DOI: 10.1210/mend-5-11-1587
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Components of a Complex Androgen-Dependent Enhancer

Abstract: Sex-limited protein (Slp) is expressed in adult male mice. A 160-basepair fragment 2 kilobases upstream of the gene serves as an androgen-dependent enhancer of chloramphenicol acetyltransferase expression in transient transfection assays in cells with endogenous or cotransfected androgen receptor. One element that is necessary, but not sufficient, for induction is a consensus glucocorticoid (or hormone) response element (HRE). This element binds to the mouse androgen receptor in vitro, but with apparent weak a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 39 publications
2
62
0
Order By: Relevance
“…We demonstrated previously that the 120-bp Slp enhancer fragment, C'A9, is hormonally responsive in CV-1 cells with cotransfected AR, but not GR, expression plasmids (1). This fragment contains several sequences similar to HREs, but only the 3'-most element, HRE-3, matches a full consensus, confers hormonal response on a reporter gene independent of additional elements, and binds full-length AR protein in vitro (2). HRE-3, however, did not account for the specificity of androgen activation, as multiple copies of this sequence inserted before a tkCAT reporter gene conferred even greater response to GR than to AR, suggesting that other elements in C'A9 must be required to delimit induction (1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We demonstrated previously that the 120-bp Slp enhancer fragment, C'A9, is hormonally responsive in CV-1 cells with cotransfected AR, but not GR, expression plasmids (1). This fragment contains several sequences similar to HREs, but only the 3'-most element, HRE-3, matches a full consensus, confers hormonal response on a reporter gene independent of additional elements, and binds full-length AR protein in vitro (2). HRE-3, however, did not account for the specificity of androgen activation, as multiple copies of this sequence inserted before a tkCAT reporter gene conferred even greater response to GR than to AR, suggesting that other elements in C'A9 must be required to delimit induction (1).…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier study of the Slp enhancer, we showed that multiple elements interact to augment, or diminish, androgen response (2). To examine the role of these elements in specific hormonal response, we used PCR to introduce clustered base changes throughout C'A9.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations